The pedunculopontine region and breathing in Parkinson's disease. Issue 5 (1st May 2019) - Hyam, Jonathan A.; Wang, Shouyan; Roy, Holly; Moosavi, Shakeeb H.; Martin, Sean C.; Brittain, John Stuart; Coyne, Terry; Silburn, Peter; Aziz, Tipu Z.; Green, Alexander L.
Abstract: Objective: Respiratory abnormalities such as upper airway obstruction are common in Parkinson's disease (PD) and are an important cause of mortality and morbidity. We tested the effect of pedunculopontine region (PPNr) stimulation on respiratory maneuvers in human participants with PD, and separately recorded PPNr neural activity reflected in the local field potential (LFP) during these maneuvers. Methods: Nine patients with deep brain stimulation electrodes in PPNr, and seven in globus pallidus interna (GPi) were studied during trials of maximal inspiration followed by forced expiration with stimulation OFF and ON. Local field potentials (LFPs) were recorded in the unstimulated condition. Results: PEFR increased from 6.41 ± 0.63 L/sec in the OFF stimulation state to 7.5 L ± 0.65 L/sec in the ON stimulation state ( z = −2.666, df = 8, P = 0.024). Percentage improvement in PEFR was strongly correlated with proximity of the stimulated electrode contact to the mesencephalic locomotor region in the rostral PPN ( r = 0.814, n = 9, P = 0.008). Mean PPNr LFP power increased within the alpha band (7–11 Hz) during forced respiratory maneuvers (1.63 ± 0.16 μ V 2 /Hz) compared to resting breathing (0.77 ± 0.16 μ V 2 /Hz; z = −2.197, df = 6, P = 0.028). No changes in alpha activity or spirometric indices were seen with GPi recording or stimulation. Percentage improvement in PEFR was strongly positively correlated with increase in alpha power ( r = 0.653, n = 14 (7 PPNr patients recorded bilaterally), P = 0.0096). Interpretation: PPNr stimulation in PD improves indices of upper airway function. Increased alpha‐band activity is seen within the PPNr during forced respiratory maneuvers. Our findings suggest a link between the PPNr and respiratory performance in PD.